Sufficiency health-wise: sustainable paths towards planetary and public health - Geiselhart, Klaus; Damm, Maik; Jeske, Niklas; Knappmann, Alexia; Nasser, Gabriela Pen; Roth, Laura Franziska; Unkels, Regine; Winkler, Andrea Sylvia; Wolf, Jennyfer; Falkenberg, Timo (Frontiers in Public Health, 2024)
Planet Earth is threatened by the human population. Energy and resource use are far beyond the planet’s carrying capacity. Planetary Health suggests an alternative idea of prosperity as the best possible human health for all within planetary boundaries. This implies giving priority to ecology because human health depends ultimately on the integrity of the global biosphere. This paper presents a Health Sufficiency Framework, based on the Doughnut Economics Model. It is meant to fuel discussions on delicate topics of the required transformations of health care and public health.
CRIS-Team Scopus Importer:2025-02-04
Keywords: health system-organization and administration; notions of health and wellbeing; planetary health; structural prevention; sustainability